Anisotropic MXene Aerogels with a Mechanically Tunable Ratio of Electromagnetic Wave Reflection to Absorption. Issue 10 (25th March 2019) - Han, Meikang; Yin, Xiaowei; Hantanasirisakul, Kanit; Li, Xinliang; Iqbal, Aamir; Hatter, Christine B.; Anasori, Babak; Koo, Chong Min; Torita, Takeshi; Soda, Yoshito; Zhang, Litong; Cheng, Laifei; et al.
Abstract: Lightweight and mechanically flexible materials that can provide efficient electromagnetic interference (EMI) shielding are highly desirable for protecting portable and smart electronic devices against electromagnetic pollution. Here, the authors report a tunable design of a three‐dimensional (3D) porous aerogel structure made of 2D transition metal carbides and a carbonitride (MXene) with a long‐range order of aligned lamellar architecture for EMI shielding. Bidirectional freeze‐casting of MXene colloidal solutions is used to fabricate robust, compressible and lightweight aerogels, and achieve orientational assembly leading to outstanding EMI shielding performance and tunable ratio of reflection to absorption. EMI shielding effectiveness (SE) of three types of MXene aerogels (Ti3 C2 Tx, Ti2 CTx, and Ti3 CNTx ) reaches 70.5, 69.2, and 54.1 dB, respectively, while keeping the compression thickness at 1 mm and a density of only ≈11.0 mg cm −3 . The highest specific SE reaches 8818.2 dB cm 3 g −1, which is among the best values reported for EMI shielding materials. More importantly, during the compression process of the MXene aerogels, the ratio of electromagnetic wave reflection to absorption increases without noticeable change of the total EMI SE. Compressible MXene aerogels with aligned layers offer an effective approach to control the electromagnetic wave absorption and reflection in EMI shielding materials. Abstract : Anisotropic MXene aerogels (Ti3 C2 Tx, Ti2 CTx, and Ti3 CNTx ) with a long‐range ordered lamellar architecture are prepared using a bidirectional freeze‐casting technique. The ratio of reflection to absorption can be adjusted simply by compressing MXene aerogels.